THE USE OF SELF-REGULATED LEARNING METHOD TO DEVELOP STUDENTS’ SPEAKING ABILITY - Farid Heriansya; M. Basri Dalle; Amar Ma’ruf (English Language Teaching Methodology, 2021)
This research aimed to know did the use of Self-Regulated Learning method improve the students’ accuracy (pronunciation) and fluency (smoothness) at the eleventh grade students of SMAN 5 Barru. The subjects of this research consisted of 33 students at the eleventh MIA 1 grade students of SMAN 5 Barru. The method in this research was quantitative research with pre-experimental research. The instruments used for collecting data namely, Speaking test in oral form. The result of the data indicated that, the students’ mean score of accuracy (pronunciation) post-test was 70.15. While the post-test was higher than mean score of pre-test, the post-test in accuracy (pronunciation) was 79.39. Moreover, based on the data analysis, t-test value was higher than the t-test table values (10.265 > 1.693). It meant that there was a significant difference. Therefore, H0 was rejected and H1 was accepted. And the students’ mean score of pre-test in fluency (smoothness) was 71.66. While, the post-test was higher than mean score of pre-test, the post-test in fluency (smoothness) was 81.06. Moreover, based on the data analysis, t-test value was higher than the t-test table values (12.590 > 1.693). It meant that there was a significant difference. Therefore, H0 was rejected and H1 was accepted. Those meant that the implementation of Self-Regulated Learning in the teaching and learning process of speaking was believed to be effective to improve the students’ speaking skills especially accuracy (pronunciation) and fluency (smoothness).